Drug Interactions in Coronary Heart Disease Patients : a Literature Review - Tamarah, Elok; Handayani, Handayani; Ferdiantoro, Andik (UNUSA Press, 2022)
Background: Patients with coronary heart disease generally receive many drugs, such as hypercholesterolemia, antianginal, antiplatelet, anticoagulants, and medications for comorbid illnesses such as antihypertension and diabetes mellitus. Concomitant administration of several types of drugs may result in drug interactions. Objective : This study aims to figure out drug interactions that might occur in using combination drugs in patients with coronary heart disease. Methods: This article review uses the Google Scholar database, published 2017-2022. The keywords used were